P. 1
Untitled

Untitled

|Views: 4|Likes:
Published by api-150839388

More info:

Published by: api-150839388 on May 30, 2013
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

09/28/2013

pdf

text

original

3 No.

1 / 2010 / — —
1
(1) A =
_
_
_
1 + 2 1 + 4
2 + 2 2 + 4
3 + 2 3 + 4
_
_
_
=
_
_
_
3 5
4 6
5 7
_
_
_
, B =
_
_
_
−1 1
−1 1
−1 1
_
_
_
(2) X = A + 3B =
_
_
_
3 5
4 6
5 7
_
_
_
+
_
_
_
−3 3
−3 3
−3 3
_
_
_
=
_
_
_
0 8
1 9
2 10
_
_
_
2
(1)
_
6
7
_
(3 1) =
_
6 · 3 6 · 1
7 · 3 7 · 1
_
=
_
18 6
21 7
_
(2)
_
3 6 1
2 1 2
_
_
_
_
0 4
3 5
1 0
_
_
_
=
_
3 · 0 + 6 · 3 + 1 · 1 3 · 4 + 6 · 5 + 1 · 0
2 · 0 + 1 · 3 + 2 · 1 2 · 4 + 1 · 5 + 2 · 0
_
=
_
19 42
5 13
_
(3)
_
_
_
1 −2 0
1 1 −1
−5 5 2
_
_
_
_
_
_
7 4 2
3 2 1
10 5 3
_
_
_
=
_
_
_
7 −6 4 −4 2 −2
7 + 3 −10 4 + 2 −5 2 + 1 −3
−35 + 15 + 20 −20 + 10 + 10 −10 + 5 + 6
_
_
_
= E
(4)
_
_
_
1
−1
2
_
_
_
(−8) =
_
_
_
−8
8
−16
_
_
_
3
(1) A
2
=
_
_
_
0 a b
0 0 0
0 0 0
_
_
_
_
_
_
0 a b
0 0 0
0 0 0
_
_
_
=
_
_
_
0 0 0
0 0 0
0 0 0
_
_
_
= O
(2) (1)
(E + A)(E −A) = E −A + A −A
2
= E + O = E
(E −A)(E + A) = E −A + A −A
2
= E + O = E (E + A)
−1
= E −A
4
_
_
_
1 2 −2 1
2 −1 6 −1
−5 0 −10 1
_
_
_
2 1 ×2
−−−−−−−→
3 +1 ×5
_
_
_
1 2 −2 1
0 −5 10 −3
0 10 −20 6
_
_
_
3 +2 ×2
−−−−−−−→
_
_
_
1 2 −2 1
0 −5 10 −3
0 0 0 0
_
_
_
_
_
_
x + 2y −2z = 1
−5y + 10z = −3
t
_
¸
¸
¸
_
¸
¸
¸
_
x = −2t −
1
5
y = 2t +
3
5
z = t
5
(1)
_
_
_
1 2 1 1 0 0
2 5 2 0 1 0
1 3 2 0 0 1
_
_
_
2 1 ×2
−−−−−−−→
3 -1
_
_
_
1 2 1 1 0 0
0 1 0 −2 1 0
0 1 1 −1 0 1
_
_
_
1 2 ×2
−−−−−−−→
3 -2
_
_
_
1 0 1 5 −2 0
0 1 0 −2 1 0
0 0 1 1 −1 1
_
_
_
1 3
−−−−−−→
_
_
_
1 0 0 4 −1 −1
0 1 0 −2 1 0
0 0 1 1 −1 1
_
_
_
A
−1
=
_
_
_
4 −1 −1
−2 1 0
1 −1 1
_
_
_
(2) A
_
_
_
x
y
z
_
_
_
=
_
_
_
1
−1
2
_
_
_
A
−1
_
_
_
x
y
z
_
_
_
= A
−1
_
_
_
1
−1
2
_
_
_
=
_
_
_
4 −1 −1
−2 1 0
1 −1 1
_
_
_
_
_
_
1
−1
2
_
_
_
=
_
_
_
4 + 1 −2
−2 −1
1 + 1 + 2
_
_
_
=
_
_
_
3
−3
4
_
_
_
6
(1) A
2
=
_
a b
c 1
__
a b
c 1
_
=
_
a
2
+ bc ab + b
ac + c bc + 1
_
= −A ⇐⇒
_
¸
¸
¸
¸
¸
¸
_
¸
¸
¸
¸
¸
¸
_
a
2
+ bc = −a
ab + b = −b
ac + c = −c
bc + 1 = −1
⇐⇒
_
¸
¸
¸
¸
¸
¸
_
¸
¸
¸
¸
¸
¸
_
a
2
+ a −2 = 0 −−− 1 ⃝
b(a + 2) = 0 −−− 2 ⃝
c(a + 2) = 0 −−− 3 ⃝
bc = −2 −−− 4 ⃝
2 ⃝, 3 ⃝ a + 2 ̸= 0 b = 0
c = 0 4 ⃝ a = −2 1 ⃝
4 ⃝ (b, c) = (−2, 1), (1, −2), (2, −1), (−1, 2) b < c (b, c) = (−2, 1), (−1, 2)
a = −2, b = −2, c = 1 a = −2, b = −1, c = 2
(2) (1) A
2
= −A = (−1)A A A
3
= (−1)A
2
= (−1)
2
A
A
4
= (−1)
2
A
2
= (−1)
3
A
A
n
= (−1)
n−1
A

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->